Sources of Electromagnetic Field in Transportation System and Their Possible Health Impacts - Zuzana Judakova; Ladislav Janousek (Communications - Scientific letters of the University of Zilina, 2019)
Exposure to electromagnetic field caused by transportation systems is a cause of concern for many people. In public and personal transport there are many sources of electromagnetic field. Plenty of dosimetric analyses of electromagnetic field carried out by various research groups found out very high exposure values in the transport. Although the measured fields in transport remain well below the general limit for public exposure as defined by ICNIRP (1998) standards, they are relatively high compared to other micro-environments in daily life, especially for children seated in the rear seat, as field strengths are comparatively high there and children are a sensitive part of the population. How long-term effects of these fields affect the human organism and what is the mechanism of action, are questions without known answers. Several studies point to the potential association of various diseases with exposure to electromagnetic field. The key to understanding the effect of the electromagnetic field on the human organism is to reveal the mechanism of action of the field.